A guide to econometrics - Kennedy, Peter, 1943-2010 (Wiley Blackwell Pub., 2008)
This is the perfect (and essential) supplement for all econometrics classes--from a rigorous first undergraduate course, to a first master's, to a PhD course. It explains what is going on in textbooks full of proofs and formulas. Kennedy's A Guide to Econometrics offers intuition, skepticism, insights, humor, and practical advice (do's and don'ts).